2006
DOI: 10.4315/0362-028x-69.8.1879
|View full text |Cite
|
Sign up to set email alerts
|

Selective Enrichment Media Affect the Antibody-Based Detection of Stress-Exposed Listeria monocytogenes due to Differential Expression of Antibody-Reactive Antigens Identified by Protein Sequencing

Abstract: Selective enrichment broths are frequently used to recover stressed Listeria cells to detectable levels, but the ability of antibodies to detect these cells from various commonly used enrichment media is unknown. In this study, a polyclonal (PAb) and monoclonal (MAb) antibody were used to examine the variation in antigen expression on healthy or stress-recovered Listeria monocytogenes cells grown in brain heart infusion broth, buffered Listeria enrichment broth (BLEB), Listeria repair broth (LRB), University o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…These results revealed that the three selected MAbs reacted more strongly to lineage I isolates than lineage II isolates grown in enrichment cultures, according to methods described in Health Canada's Compendium of Analytical Methods. Unlike previous studies of potential diagnostic surface proteins which reported reduced protein expression under specific conditions (10,11,36,37), the stable expression of LMOf2365_0639 in enrichment culture makes it a suitable candidate biomarker.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…These results revealed that the three selected MAbs reacted more strongly to lineage I isolates than lineage II isolates grown in enrichment cultures, according to methods described in Health Canada's Compendium of Analytical Methods. Unlike previous studies of potential diagnostic surface proteins which reported reduced protein expression under specific conditions (10,11,36,37), the stable expression of LMOf2365_0639 in enrichment culture makes it a suitable candidate biomarker.…”
Section: Discussionmentioning
confidence: 63%
“…Geng et al previously developed PAbs against four L. monocytogenes proteins, one of which was Lmo0610, the homologue of LMOf2365_0639 (36). Their study, which utilized Western blotting, revealed weak expression of Lmo0610 in L. monocytogenes V7 (serotype 1/2a) cultured in Fraser, UVM, and BHI broths.…”
Section: Discussionmentioning
confidence: 99%
“…Several previously reported studies classified NamA with primary functions closely associated with the bacterial surface based on the presence of its LysM peptidoglycan binding domains (3,6,7,10), its detection at the bacterial surface (8,52), and its ability to serve as an immunoreactive epitope in L. monocytogenes detection studies (19,20,44). Other studies, however, have detected NamA in supernatant fractions derived from L. monocytogenes strains containing a mutationally activated form of the virulence regulator PrfA [PrfA(L140F)] as well as in wild-type supernatants in comparison to secA2 mutants (33,50), although those studies did not determine if secreted NamA was functionally active.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were transferred onto polyvinylidene difluoride (PVDF) membranes at 1.0 A (constant) for 1 h. All membranes were blocked for 1 h in PBS (Gibco, Carlsbad, CA) containing 0.05% Tween (PBST) and 5% milk. Membranes were incubated with a 1:2,500 dilution of monoclonal antibody C11E9 in PBST (a kind gift of Arun Bhunia), which is known to specifically recognize NamA (19), or a 1:500 dilution of monoclonal antibody against internalin A (Toxin Technologies, Sarasota, FL) at 4°C overnight with shaking, followed by three additional washes with 30 ml of PBST for 10 min each. A 1:2,500 dilution of secondary goat anti-mouse antibody conjugated to alkaline phosphatase (Southern Biotech, Birmingham, AL) was incubated with shaking for 2 h at room temperature, followed by three additional 10-min washes in PBST.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation